2018
DOI: 10.1159/000493661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid on Mineral and Bone Disorders in Hemodialysis Patients: a Systematic Review and Meta-Analysis

Abstract: Background/Aims: Hemodialysis (HD) patients often have inadequate nutrition, especially with respect to ascorbic acid (AA). It is reported that every HD session may cause a 50%– 75% decrease in plasma AA levels. Some studies have shown that supplementation of AA can change the outcome of chronic kidney disease-mineral bone disorders (CKD-MBD), but the effect of AA on HD patients with CKD-MBD remains controversial. Consequently, we decided to perform a meta-analysis to evaluate the efficacy of AA supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Therefore, it is important to control the plasma calcium, phosphate, and parathyroid hormone levels in non-hemodialysis CKD and hemodialysis patients [42]. Through a systematic review and meta-analysis, Ke et al [43] reported that vitamin C supplementation in CKD patients had no positive effect that influenced the plasma phosphate or parathyroid hormone levels, but it increased plasma calcium levels in the short term. In the present study, we did not detect any correlation between plasma ascorbate and plasma calcium, phosphate, and parathyroid hormone levels in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to control the plasma calcium, phosphate, and parathyroid hormone levels in non-hemodialysis CKD and hemodialysis patients [42]. Through a systematic review and meta-analysis, Ke et al [43] reported that vitamin C supplementation in CKD patients had no positive effect that influenced the plasma phosphate or parathyroid hormone levels, but it increased plasma calcium levels in the short term. In the present study, we did not detect any correlation between plasma ascorbate and plasma calcium, phosphate, and parathyroid hormone levels in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to control the plasma calcium, phosphate, and parathyroid hormone levels in the non-hemodialysis CKD and hemodialysis patients [41]. Through a systematic review and meta-analysis, Ke et al [42] have reported that vitamin C supplementation in CKD patients has no positive effect that influence the plasma phosphate or parathyroid hormone levels, but it increase plasma calcium levels in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid supplements transiently increased serum calcium level, without significantly affecting serum phosphate and PTH levels. Its use in CKD patients is not supported [ 35 ].…”
Section: Nonpharmacological Approachmentioning
confidence: 99%